On the Relationship Between Financial Distress and ESG Scores - Christian Lohmann; Steffen Möllenhoff; Sebastian Lehner (Corporate Social Responsibility and Environmental Management, 2025)
This empirical study analyzes the relationship between a company's financial distress obtained from a bankruptcy prediction model and ESG scores from Refinitiv, MSCI, ESG Book, and Moody's ESG. Applying a nonparametric regression technique on panel data of listed US companies for 2003–2022 reveals a pronounced and statistically significant U-shaped relationship between financial distress and ESG scores. Financially distressed companies exhibit high ESG scores. Further empirical analysis shows that the most plausible interpretation is that companies anticipate their upcoming financial distress and intensify ESG-supporting disclosures to manage their ESG scores upward. The empirical results underline the importance of including the financial health of a company in ESG assessments. Only by taking into account both the ESG performance and the financial sustainability of a company is it possible to assess responsible corporate governance.
Keywords: 650; ESG; ESG score; financial distress; nonparametric regression; shareholder-stakeholder orientation